A PRELIMINARY LOOK AT THE STRUCTURAL DIFFERENCES OF HIGHER EDUCATION CLASSROOM COMMUNITIES IN TRADITIONAL AND ALN COURSES - Rovai, Alfred P. (Online Learning, 2002)
This preliminary study again provides evidence that it is the method and not the media that matters the most in learning effectiveness. The present work examines classroom community in order to determine how sense of community differs between students enrolled in traditional face-to-face and those enrolled in asynchronous learning network (ALN) courses. Subjects consist of 326 adult learners who were enrolled in a mix of 14 undergraduate and graduate courses at two urban universities. As operationalized by the Sense of Classroom Community Index (SCCI), there appears no significant difference in classroom community between the two groups of subjects. However, a discriminant analysis shows a significant overall difference in community structure between the two groups. Variations between groups on feelings of similarity of needs, recognition, importance of learning, connectedness, friendship, thinking critically, safety, acceptance, group identity, and absence of confusion are the characteristics contributing mostly to this difference in learning effectiveness.